Efficacy and safety of mirabegron in the treatment of overactive bladder syndrome after radical prostatectomy: a prospective randomized controlled study - Li, Wang; Lin, Yanduo; Xie, Hong; Fu, Qiang; Chen, Rong; Hu, Xiaoyong; Huang, Jianwen; Wang, Jihong; Yang, Ranxing (Frontiers in Oncology, 2023)
Objectives：To evaluate the effects of mirabegron in the treatment of overactive bladder syndrome (OAB) after radical prostatectomy (RP). Patients and Methods：A total of 108 post-operative RP patients were randomly assigned to either the mirabegron (study) or the placebo (control) group. The Overactive Bladder Syndrome Self-Assessment Scale (OABSS) was selected as the primary endpoint, and the International Prostate Symptom Score (IPSS) and QOL score were selected as secondary endpoints. Statistical analysis was performed using IBM SPSS Statistics 20, and the treatment effects were compared between the two groups using independent samples t-test. Results：In total, 55 patients were included in the study group and 53 patients in the control group. The mean age was(70.08 ± 7.54)years. There was no statistical difference in the baseline data between the two groups. OABSS scores decreased significantly in the study group compared to the control group during drug treatment (6.67 ± 1.06 vs. 9.14 ± 1.83, p < 0.01) and were better than the control group during the follow-up at week 8 and week 12. In addition, the decrease in IPSS scores (11.29±3.89 and 15.34±3.54, p<0.01) and the increase in QOL scores (2.40±0.81 vs. 3.20±1.00) were statistically significant in the study group. And the patients in the study group had better improvement in voiding symptoms and quality of life than the control group during the follow-up period. Conclusion：Daily administration of 50 mg mirabegron after RP surgery significantly improved the symptoms of OAB after surgery with fewer side effects. Additional randomized controlled trials should be conducted in the future to further evaluate the efficacy and safety of mirabegron.